Evaluation of the Education for All-Fast Track Initiative Programme in Cameroon (2014)
The universalisation of primary education made schooling obligatory and free in Cameroon. This resulted in overcrowded classrooms and poor achievement in Language (English and French) and Mathematics. The World Bank (2007) introduced an intervention programme, Education for All-Fast Track Initiative (EFA-FTI) programme, by recruiting 37,200 qualified teachers to reduce class size and teacher-pupil ratio and improve pupils‘ achievement. However, since the inscription of the programme, no study has investigated Cameroon‘s progress towards achieving the EFA-FTI goals. The study, therefore, evaluated the effect of class size and teacher-pupil ratio, teacher effectiveness, teacher job satisfaction, teacher qualification, teacher experience, school location and school type, school infrastructure and pupils‘ proficiency in language on pupils‘ achievement in mathematics. The research was an ex-post facto type which adopted the Context Input Process Product (CIPP) Model. Schools were stratified along types (EFA-FTI and non EFA-FTI) and locations (urban and rural). Simple random sampling was used to select 40 government primary schools from five regions in two educational zones; Francophone (three) and Anglophone (two) with 50 primary six pupils from each class (classes with less than 50 pupils were all taken). In all, 1807 pupils, 40 schools, 40 teachers, 40 head teachers, a World Bank representative, one Government representative and 10 National Pedagogic Inspectors of Education participated in the study. Seven validated instruments were used. Classroom Observation Rating Scale (r=0.86), Head Teacher Material Resources Checklist, Teacher Job Satisfaction Questionnaire (r=0.76), Pupils‘ Evaluation of Teacher Effectiveness Scale (r=0.78), Language Proficiency Test (r=0.72), Pupils Achievement Test in Mathematics (r=0.76) and In-Depth Interview Schedule (r=0.76). Data were analysed using descriptive and inferential statistics; mean, standard deviation, t-test, Pearson Product Moment correlation and multiple regression at p≤ 0.05 level, while the qualitative data were thematically analysed There was a significant mean difference in class size and teacher-pupil ratio between the EFA-FTI and non EFA-FTI schools (57:75; 1:57 and 1:75, respectively). Pupils‘ achievement in mathematics was negatively related to teacher effectiveness (r=-.017). Pupils from the EFA-FTI schools were more proficient in language (M=54.01) than those from non EFA-FTI schools (M=50.23) but not significantly different in achievement in mathematics. The 10- predictor variables predicted achievement in mathematics (R2=.605, R2 adj =.486, F(9,30)=5.104). The three most significant variables in predicting pupils‘ achievement in mathematics were: proficiency in Language (ß =.627); teacher working experience (ß =-.243) and teacher effectiveness (ß= -.275). High language proficiency (M =78.78) had a high mathematics score (M=64.92) and a low language proficiency (M=42.12) had a low mathematics score (M=39.56). There was attrition due to posting allocations because teachers were often absent in the schools where they were posted to, particularly in the rural areas. The Education For All-Fast Track Initiative programme increased teacher quality and quantity and improved pupils‘ proficiency in Language, did not meet the objective of reducing class sizes (40) and Teacher-pupil ratios (1:40) and did not improve pupils‘ achievement in mathematics in the schools. To reduce attrition, newly posted teachers should sign an undertaking to remain at their places of work for three years before applying for transfer.